THE INFLUENCE OF THE SCHOOL ENVIRONMENT ON THE FORMATION OF CLASS STUDENTS CHARACTER IV STATE ELEMENTARY SCHOOL UPTD NO 122384 - Eva Pasaribu; Henriko Sihotang (SENSEI RESEARCH CENTER, 2024)
This research aims to determine the relationship between the influence of the school environment on the character formation of class IV students at SD 122384 in the 2023/2024 academic year. In this research, researchers used quantitative research. The population in this study was all 16 class IV students using the entire population as the research sample. The data collection process uses observation instruments, questionnaires and documentation, using data analysis techniques of validity testing, reliability testing, normality testing, descriptive statistical linearity testing and hypothesis testing. The results of this research show that the tcount ? ttable value is 3.574 ? 0.468 and with a significance value of 0.003 ? 0.05 and produces an R Square of 0.471, so it is concluded that the school environment has an influence of 47.1% on the character formation of class IV students at State Elementary School 122384.